X-ray investigations of solid solutions of monocalcium aluminate and monostrontium aluminate important phases in cement and phosphorescence materials. Issue 2 (15th May 2014) - Pöllmann, H.; Kaden, R.
<x content-type="archive" xml:space="preserve">Abstract</x> Calcium monoaluminate is the main phase in calcium aluminate cements and participates in the hydration, forming calcium aluminate hydrates. The amount of incorporation of foreign ions influences the hydration behaviour. Strontium aluminate is an important phase in producing phosphorescent materials when doped with rare-earth elements (REE) such as Eu, Dy, and La. These monoaluminates occur in different forms. Monocalcium aluminate forms a monoclinic and an orthorhombic modification, whereas monostrontium aluminate forms a monoclinic low-temperature and a hexagonal high-temperature form. Monoclinic calcium monoaluminate and monoclinic strontium aluminate form a partial solid-solution series. The hydration behaviour of different solid solutions was also investigated using calorimetry. The newly formed strontium aluminate hydrates could be identified while similar strontium aluminate hydrates are formed. Solid solutions of strontium- and calcium-aluminate hydrates will be investigated.